Influence of plant species on triclosan removal and associated microbial communities in the vertical-flow constructed wetland - Naveen Chand; Vineet Singh; Surindra Suthar (Cleaner Water)
This study investigated plant species' role in removing triclosan (TCS) and functional bacterial diversity in the rhizosphere of vertical flow-constructed wetlands (VFCWs). Two VFCWs with similar configurations but different plants i.e., Colocasia (CB-VFCW) and Typha (TB-VFCW) were established and TCS removal was recorded under four cycles of 216 hrs HRT. The TB-VFCWs showed the maximum average TCS removal (89.41 %) during studied HRT than CB-VFCWs (79.4 %) (p > 0.05). The respective removal of COD, NH4+-N and NO3- -N was found to be 89.5 %, 84.8 % and 77.5 % in TB-TFCW and 79.88 %, 87.16 % and 66.25 % in CB-VFCWs, suggesting significant variations between VFCWs. 16S data analysis suggested variations between CB-VFCW and TB-VFCW for bacterial abundance, species diversity and richness. Proteobacteria especially the Beta subdivision found to be the dominant bacterial community showing positive correlations with TCS reductions. Results found that plant species selection could be a valuable approach for the enrichment of ecologically relevant microbiota in VFCWs involved in organic pollutant removals in such systems.